Monochorionic triplet with concordant congenital cardiac defects - Ibrahim Aliyu (Wolters Kluwer Medknow Publications, 2013)
The chances of congenital cardiac defects are often increased in multiple birth orders. However, there is a paucity of data on its incidence amongst triplets in Nigeria. Here is a report of a set of triplet with concordant atrial septal defects and the third triplet found to have a concomitant ventricular septal defect.